Prilaku Kesehatan Reproduksi Dalam Mencegah Pernikahan Usia Dini Melalui Organisasi Sosial “Sekaa Truni” Di Daerah Urban Dan Rural Bali - Sugiartini, Desak Ketut; Bukian, Putu Agus Windu Yasa; Kusuma Dewi, Putu Dian Prima (Jayapangus Press, 2023)
Adolescence is a period that is very vulnerable to negative things in the environment due to great curiosity and lack of emotional maturity. Risky sexual behavior is premarital sexual activity carried out consciously by teenagers, resulting in disruption to the physical, mental and social health of teenagers. A marriage age that is too early can result in increased cases of divorce due to a lack of awareness of responsibility in married life for husband and wife. Early marriage has an impact on teenagers, especially teenage girls, with the physical, psychological and economic impacts they experience. The aim of this research is to analyze reproductive health behavior to prevent early marriage through sekaa truni as a form of local wisdom owned by the Balinese people. Research regarding the role of local Balinese wisdom in preventing early marriage has never been carried out so far. The results of the research from 120 respondents who responded showed that reproductive health knowledge in reproductive health knowledge was in the good category as much as 94 (78.3%), negative attitudes towards reproductive health behavior were 68 (56.7%) and reproductive health behavior was classified as not risky as much as 10 (8.33%) with parenting styles. Most of them are democratic. A negative attitude towards non-risky reproductive behavior is a variable that increases the chances of risky reproductive behavior occurring up to 6 times (adjusted OR 6 p=0.02 CI: .21-29.59). The results of in-depth interviews show that teenagers Women have good protection and insight into early marriage when supported by parenting, attention and support from the environment and parents.